Genetic Association of Olanzapine Treatment Response in Han Chinese Schizophrenia Patients - Zhou, Wei; Xu, Yong; Lv, Qinyu; Sheng, Yong-hui; Chen, Luan; Li, Mo; Shen, Lu; Huai, Cong; Yi, Zhenghui; Cui, Donghong; Qin, Shengying (Frontiers in Pharmacology, 2019)
Olanzapine is a second-generation antipsychotic medication, which plays a predominant role in current treatment of schizophrenia. It has been observed that the olanzapine response in schizophrenia treatment is different across individuals. However, predicting such individual-specific olanzapine response requires deep understanding of relevant biomarkers. Here, we performed an integrative investigation on 238 Han Chinese schizophrenia patients, aiming to identifying hidden predictive biomarkers that were related to the efficacy of olanzapine treatment. 143 genes were sequenced from 79 Han Chinese schizophrenia patients using HaloPlex technology. The following analysis indicated that there were 12 single nucleotide polymorphisms (SNPs) were significantly associated with drug response of olanzapine. These novel SNPs were verified in 159 other patients (independent cohort) as well as in the overall 238 patients that were composed of two cohorts we used in this study using MassARRAY platform. The results showed that 2 SNPs were associated with the olanzapine response in both independent cohort (rs324026, P = 0.023 and rs12610827, P = 0.043, respectively) and total cohort (rs324026, adjust P = 0.014 and rs12610827, adjust P = 0.012, respectively). This study provides systematic analyses of genetic variants that were associated with olanzapine responses in Han Chinese schizophrenic patients. Our discovery of genetic biomarkers in olanzapine-response will shed light on future personalize olanzapine treatment design for Han Chinese schizophrenic patients.